Configuration of robust manufacturing systems - Heinicke, Matthias (Cranfield University Press, 2013)
Considering the increasing turbulence in the markets, many companies are faced with the task of responding to changes in customer demand in a flexible and timely manner. A variety of current research projects in terms of configuration of production systems deals with the increasing flexibility of several elements of a production system or the entire system, to meet the need for flexible responses. Furthermore, there is the avoidance or reduction of any kind of waste, including the creation of standards for the information and material flow processes at the heart of the company's efforts. Against this background, also organisationally robust processes are increasingly becoming the focus of operational actors. This paper points out the possibilities of influencing production systems and what characteristics exist regarding the requirement of structural changes. In this context, production control by defined loops and checking structural performance are indicators relevant to the focus of following considerations.
Keywords: robust manufacturing system; exertion of influence on manufacturing systems; manufacturing control